From communicative strategies to pragmatic motivations - Bulatetska, Lyudmyla; Булатецька, Людмила (Східноєвропейський національний університет імені Лесі Українки, 2014)
The article deals with the notion of involvement, which has the dynamic nature and varies within the boundaries of empathy, sympathy, (self)withdrawal, antipathy. Involvement is defined as a cognitive notion with the prevailing characteristics of cognitive distancing or approximation in interaction. Generally recognized is the point of view that involvement is a gradual phenomenon. It fluctuates depending on the activity of interlocutors. What follows from it is the absolute mutual trust of communicative partners to one another on the one hand or giving up and disregard the communication by both sides on the other. Such a shift of communicative parameters of communicative activity is a direct reflection of the change in the focus of orientation which directly depends on the focus of interest. The general vision of involvement is widening and depends on what goes to the focus of orientation. Existing approaches are reduced to the following three: a) involvement of the speaker and listener to the information of the topic (as individual participants); b) involvement of the community members (as mass participants); c) involvement of the topic on the parameter of its informativity and validity of the problem. Degrees of involvement are controlled by the communicative strategies of interlocutors, they re-frame the configuration of notions of empathy, sympathy, (self)withdrawal and antipathy, assisting in achievement of maximal communicative result and coincidence of positions of opposite sides.

У статті розглядається комунікативна сутність ЗАЛУЧЕННЯ як градуальної величини, яка видозмінюється в діапазоні: емпатія – симпатія – (само)усунення – антипатія. Залученість визначається як когнітивна сутність із переважальними характеристиками на нестабільність комунікативної дистанції. Загальновизнаною є точка зору про те, що залученість – це градуальне явище. Його флактуація залежить від комунікативної активності комунікантів. Як результат отримуємо абсолютну взаємну довіру партнерів, з одного боку, і відмову та недовіру один до одного – з іншого. Такий зсув параметрів комунікативної активності – пряме відображення в зміні фокусу орієнтації, що безпосередньо залежить і від фокусу зацікавленості. Загальне бачення залученості розширюється і залежить від того, що попадає в промінантне поле. Нинішні підходи зводяться до трьох наступних: а) залученість мовця і слухача до предмета думки мовця (індивідуальні учасники); б) залученість членів колективу (учасники мовного співтовариства); в) залученість самого предмету думки мовця за параметром його інформативності й актуальності проблеми. Ступінь залученості контролюється стратегіями комунікантів, завдяки яким рефреймується конфігурація емпатії, симпатії, (само)усунення й антипатії. Це сприяє досягненню максимального комунікативного результату за збігом позицій протилежних сторін
Від комунікативних стратегій до прагматичних мотивацій
Keywords: involvement; intention; focus of orientation; vantage point; empathy; sympathy; (self)withdrawal; antipathy; prediction; anticipation; dynamic equilibrium; залученість; інтенція; фокус орієнтації; точка відрахунку; симпатія; емпатія; (само)усунення; антипатія; передбачуваність; очікуваність; динамічний еквілібріум